2016
DOI: 10.1038/cti.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Dietary metabolites and the gut microbiota: an alternative approach to control inflammatory and autoimmune diseases

Abstract: It is now convincingly clear that diet is one of the most influential lifestyle factors contributing to the rise of inflammatory diseases and autoimmunity in both developed and developing countries. In addition, the modern 'Western diet' has changed in recent years with increased caloric intake, and changes in the relative amounts of dietary components, including lower fibre and higher levels of fat and poor quality of carbohydrates. Diet shapes large-bowel microbial ecology, and this may be highly relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 125 publications
(138 reference statements)
4
145
1
6
Order By: Relevance
“…The disturbance of gut microbiota will affect the levels of TMA and TMAO, and further affect the body's immune function, which is in agreement with reported results (Kamada, Seo, Chen, & Núñez, 2013;Richards, Yap, McLeod, Mackay, & Mariño, 2016). The model group showed lower level of TMAO, which suggested that Cy had an effect on disturbance of gut microbes.…”
Section: Gut Microbiota-related Metabolismsupporting
confidence: 81%
“…The disturbance of gut microbiota will affect the levels of TMA and TMAO, and further affect the body's immune function, which is in agreement with reported results (Kamada, Seo, Chen, & Núñez, 2013;Richards, Yap, McLeod, Mackay, & Mariño, 2016). The model group showed lower level of TMAO, which suggested that Cy had an effect on disturbance of gut microbes.…”
Section: Gut Microbiota-related Metabolismsupporting
confidence: 81%
“…Such maladies are often associated with dysregulated inflammatory responses, or with susceptibility to damage caused by such responses. As such, it has been postulated that altering the diet or the microbiota may augment damage tolerance and limit pathology (37). We and others have implicated indoles and other products of bacterial TnaA in protective responses to damage by stressors and pathogens in both C. elegans and mammals (11)(12)(13)16) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Youth is characterized by the capacity to move without impairment, to reproduce, to tolerate diverse environmental stressors with minimal attendant damage (damage tolerance), and to regenerate following damage, conditions that define healthspan (31)(32)(33) implicated in various disease states, including inflammatory bowel disease, obesity, and diabetes (34)(35)(36)(37). Such maladies are often associated with dysregulated inflammatory responses, or with susceptibility to damage caused by such responses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of probiotics to improve metabolic profiles (21,22), and reduce inflammatory factors (23)(24)(25) and oxidative stress biomarkers (26,27) has been investigated. Microbes in the gut contribute to extraction of energy from food and should be considered an environmental factor involved in obesity and related disabilities, such as insulin resistance, diabetes, and cardiovascular disease (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%